2017
DOI: 10.1007/s00436-017-5621-9
|View full text |Cite
|
Sign up to set email alerts
|

Myxobolus linzhiensis n. sp. (Myxozoa: Myxobolidae) from the gill filament of Schizothorax oconnori Lloyd (Cyprinidae: Schizothoracinae) in Tibet, China: morphological and molecular characterization

Abstract: In this report, a new myxosporean species, Myxobolus linzhiensis n. sp. (Cnidaria: Myxozoa: Bivalvulida), was described from the endemic cyprinid Schizothorax oconnori inhabiting the Yarlung Tsangpo River in the Tibetan plateau, China. The whitish ellipsoidal plasmodia of M. linzhiensis n. sp. grew under the epithelium of gill filaments, 1.7-mm long and 0.4-mm wide, and were found in the 3 of 8 examined S. oconnori (37.5%). Mature spores appeared suborbicular in frontal view, fusiform shaped in lateral view wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…By its large plasmodia and the shape and size of the spores, M. szekelyensis resembles the best to the species M. linzhiensis described by Li et al (2017) from Schizothorax oconnori, but in plasmodia of the latter species, there is only a small iodinophilous vacuolum, and polar fil- and Gupta and Kaur (2017a), in which reported that largesized plasmodia can result in more than 50% damage to the gills, eventually affecting the respiratory system. Such damages induce less functioning of gills and accessory respiratory system by reducing the surface of respiratory system as described by Eissa (2002) and Sabri et al (2010).…”
Section: Morphological Comparisonmentioning
confidence: 86%
“…By its large plasmodia and the shape and size of the spores, M. szekelyensis resembles the best to the species M. linzhiensis described by Li et al (2017) from Schizothorax oconnori, but in plasmodia of the latter species, there is only a small iodinophilous vacuolum, and polar fil- and Gupta and Kaur (2017a), in which reported that largesized plasmodia can result in more than 50% damage to the gills, eventually affecting the respiratory system. Such damages induce less functioning of gills and accessory respiratory system by reducing the surface of respiratory system as described by Eissa (2002) and Sabri et al (2010).…”
Section: Morphological Comparisonmentioning
confidence: 86%